THE EFFECT OF GREEN ACCOUNTING AND FINANCIAL PERFORMANCE ON TAX AVOIDANCE IN THE MINING SECTOR LISTED ON THE IDX IN 2021-2025 - Aldi Prastiyo; Putri Awalina; Moch. Wahyudi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Main Objective - This study aims to analyze the influence of green accounting and financial performance on tax avoidance in the mining sector listed on the IDX in 2021-2025. Method - The sample used in this study was 10 mining companies listed on the IDX for the 2021–2025 period. Total observations: 50 data. The method used in this study was a quantitative method using SPSS. Main Findings - The results of this study reveal that green accounting variables influence tax avoidance, while financial performance does not. Theoretical and Policy Implications - This study emphasizes the position of green accounting and financial performance not as independent factors, but as complementary elements in shaping tax management strategies. Therefore, the practical implication of the third hypothesis is the importance for companies to balance their focus on sustainability and financial performance, as both contribute simultaneously to fiscal policy and tax avoidance decisions. Research Novelty - This study's novelty is that it targets in the mining sector listed on the IDX in 2021-2025.